A compact multi‐slots loaded gap coupled CP antenna with DGS for WLAN/WiMAX applications. Issue 12 (8th September 2020) - Verma, Mahesh K.; Kanaujia, Binod K.; Saini, Jai P.; Singh, Padam
Abstract: In this article a novel compact circularly polarized slotted gap coupled semi‐circular patch antenna is presented for WLAN and WiMAX applications. The prototype of the designed antenna is fabricated with an area of 42.5 × 42.5 mm 2 . The circular polarization (CP) radiation is obtained by introducing a square ring slot defect in the ground plane whereas wide impedance bandwidth is achieved by gap coupled semi‐circular patches with L‐shaped slots. In order to improve the antenna bandwidth with better impedance matching an inclined slot is etched from the center of the patches. Further, to understand the effect of slots on antenna characteristics a parametric study is conducted. The measured impedance bandwidth (|S11 | ≤ −10 dB) and axial ratio bandwidth for AR ≤ 3 dB of the proposed antenna are 83.08% (5.15‐12.47 GHz) and 34.29% (4.30‐6.08 GHz), respectively. The gain of the antenna is > 4 dBi within the CP band. The measured and simulated results are well accepted.